Mitochondrial Genome of Endangered Hylobatidae, Hylobates lar, and Hylobates agilis, of Peninsular Malaysia - Roberta Chaya Tawie, Tingga; Millawati, Gani; Badrul Munir, Md Zain (Malaysian Society of Applied Biology, 2024)
Hylobates agilis and Hylobates lar, members of the family Hylobatidae, are classified as endangered species in Malaysia due to threats such as population decline and habitat loss. The aim of this study was to sequence and characterize the mitochondrial genome of H. lar and H. agilis. This study reported the total length of mitogenome of H. agilis and H. lar to be 16,473 and 15,949 base pair (bp), respectively. Each sequence contained 13 proteincoding sequences, 2 rRNAs, 22 tRNAs, and a control region D-loop (H. agilis); meanwhile for H. lar, there are 13 protein-coding sequences, 2 rRNAs, 19 trNAs, and a control region D-loop. Phylogenetic analysis showed both species formed a strong monophyletic clade within Hylobates grouping. Mitogenomic data of this study is essential for future references in evolutionary biology and conservation management of endangered Malaysian gibbons in captivity.